2019
DOI: 10.25186/cs.v14i4.1619
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF STEEPING ROBUSTA COFFEE BEANS ON MONOCYTES: EXPRESSION OF IL-1β AND TNF-α AGAINST Streptococcus mutans

Abstract: Adhesion, IL–1β, TNF–α are components that affect in inflammation. So, the effect of steeping green and black Robusta coffee beans to adhesion of <em>Streptococcus mutans</em> on this components. This study used monocytes isolated from healthy human peripheral blood using Ficoll-Hypaque centrifugation method. Monocytes were divided into eight groups, i. e. (i) Control group (untreated monocytes), (ii) <em>Streptococcus mutans</em> group (monocytes + <em>S. mutans</em>), (iii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, coffee has a very complex chemical composition. In addition to caffeine, coffee contains many other substances that might act as antioxidants (Damat et al, 2019;Halvorsen et al, 2002;Moriera et al, 2013;Natella et al, 2007;Suryono et al, 2020) and antiinflammation (Cardenas; Quesada; Medina, 2011; Dewanti et al, 2019;Kempf et al, 2010;Moriera et al, 2013) that might counteract the adverse effect of caffeine. Due to its rich antioxidant and anti-inflammatory content, it has been hypothesized that coffee consumption might be of benefit to cardiovascular health since oxidation and inflammation represent the important mechanisms in coronary artery disease (Rafieian-Kopaei, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, coffee has a very complex chemical composition. In addition to caffeine, coffee contains many other substances that might act as antioxidants (Damat et al, 2019;Halvorsen et al, 2002;Moriera et al, 2013;Natella et al, 2007;Suryono et al, 2020) and antiinflammation (Cardenas; Quesada; Medina, 2011; Dewanti et al, 2019;Kempf et al, 2010;Moriera et al, 2013) that might counteract the adverse effect of caffeine. Due to its rich antioxidant and anti-inflammatory content, it has been hypothesized that coffee consumption might be of benefit to cardiovascular health since oxidation and inflammation represent the important mechanisms in coronary artery disease (Rafieian-Kopaei, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the effect on the prevention of opportunistic infection, it is important to study SFDRGC role on inflammatory immune response against C. albicans. Previously, Dewanti et al, (2019) have shown that steeping of Robusta ground coffee could reduce inflammation against oral microorganism Streptococcus mutans. In addition, clinical trials and epidemiological studies were needed to study further.…”
Section: Discussionmentioning
confidence: 99%
“…Indonesia is the fourth world coffee exporter after Brazil, Colombia, and Vietnam [1]. Coffee is one of the leading commodities in Indonesia, with positive impacts in socio-economic [2], health science [3,4], and others. Coffee performance is not only in beans.…”
Section: Introductionmentioning
confidence: 99%